Bog bodies uncovered : solving Europe's ancient mystery - Aldhouse-Green, Miranda J. (Miranda Jane) (Thames & Hudson, 2015)
It is time for a new book about bog bodies: the number of known bodies is growing. Lindow Man, the famous 'Pete Marsh' discovered in Cheshire in the 1980s, has been joined by new finds from Ireland and elsewhere. Who were these unfortunate people, and why were they killed?